1967
DOI: 10.1002/ajpa.1330270103
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the musculus palmaris longus studied in vivo in some Amazon Indians

Abstract: The frequency of the Musclus palmaris longus was studied by observing its tendon in vivo in 379 Amazon Indians belonging to the following tribes: Tucano, Tariana, Tiriyo, Desana, Piratapuya, Macu and Arapaso. The muscle was not observed in 14 individuals (3.7% ± 1.0) either unilaterally or bilaterally and in 24 of 758 limbs (3.1% ± 0.6). No statistically significant difference was observed in the frequency of the muscle among the different tribes. Bilateral absence was significantly more frequent than the unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 15 publications
4
43
0
Order By: Relevance
“…The right absence of PL was 2 % in Amazon Indians (Machado & Di Dio, 1967), although this ratio was low, it was close to the results of Mbaka & Ejiwunmi (2009) (2.5%) and Kapoor et al (3 %) studies. The right absence was found as 11.9 % and 10.2 % in the Iranian and Egyptian populations, respectively (Abdolahzadeh Lahiji et al, 2013;Raouf et al).…”
Section: Discussionsupporting
confidence: 90%
“…The right absence of PL was 2 % in Amazon Indians (Machado & Di Dio, 1967), although this ratio was low, it was close to the results of Mbaka & Ejiwunmi (2009) (2.5%) and Kapoor et al (3 %) studies. The right absence was found as 11.9 % and 10.2 % in the Iranian and Egyptian populations, respectively (Abdolahzadeh Lahiji et al, 2013;Raouf et al).…”
Section: Discussionsupporting
confidence: 90%
“…In other ethnic groups lower percentages of agenesis could be observed, 3.7% among the Amazon natives of the South America (Machado & DiDio, 1967), 4.6% for the Chinese (Sebastin et al), 1.5% for African black (Gangata), 11.5% in South Africans miscegenated (Ndou et al, 2010) and 36.8% for the Bahraini population in the Arabian Gulf (Sater et al, 2010). Among the Indian population, Kapoor et al found 17.2% of total agenesis, a value close to the one found by Agarwal (2010), which was 20.2% in a recent study with Indians.…”
Section: Discussionmentioning
confidence: 85%
“…Unilateral agenesis was seen in 76 (15.2%) and bilateral [12]. The prevalence of absence of PL in the Chinese populace was 4.6% (bilateral 1.2% and unilateral 3.3%) [13]. While the prevalence of absence of PL on both unilaterally and bilaterally was 26.6% in Turkish subjects.…”
Section: Resultsmentioning
confidence: 91%